2017
DOI: 10.2174/1874834101701010048
|View full text |Cite
|
Sign up to set email alerts
|

Study on Wellbore Stability of Shallow Sediments in Deepwater Drilling

Abstract: Background:The deepwater shallow formation has low fracture pressure and narrow safe window of mud density, which results in a high risk of wellbore instability in this kind of formation. Objective:Without considering the plastic state of shallow formation around the borehole or the influence of in-situ stress difference on wellbore stability, the prediction accuracy of the traditional wellbore stability analysis models are relatively low. This paper can provide a reliable method to accurately predict the safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A deep water drilling water pipe system and vibration active control system including a sensor, actuator, signal processing module control module for monitoring longitudinal and lateral vibration of the drain water pipe system. Zhang et al found that although deep-water formations have their own characteristics compared with land and shallow-water formations, it is the same in wellbore stability research methods [6]. Zheng et al studied the influence of water depth on the fracture pressure and found that the fracture pressure of the deepwater wellbore is relatively close to the pressure of the overlying strata, but no specific model [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A deep water drilling water pipe system and vibration active control system including a sensor, actuator, signal processing module control module for monitoring longitudinal and lateral vibration of the drain water pipe system. Zhang et al found that although deep-water formations have their own characteristics compared with land and shallow-water formations, it is the same in wellbore stability research methods [6]. Zheng et al studied the influence of water depth on the fracture pressure and found that the fracture pressure of the deepwater wellbore is relatively close to the pressure of the overlying strata, but no specific model [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the air drilling practice in Karamay oilfield, it is put forward that the influencing factors of wellbore stability in air drilling include mechanics and chemistry (Li 1994). The concentration and chemical properties of liquid phase in mist drilling effected on borehole stability were evaluated by laboratory experiments (Huang et al 1995). The von Mises failure criterion is used to get reliable prediction of the collapse pressure (Guo and Ghalambor 2002).…”
Section: Introductionmentioning
confidence: 99%